Finite Element Solution of an Unsteady MHD Flow through Porous Medium between Two Parallel Flat Plates - AbdelLatif Sa’adAldin; Naji Qatanani (Journal of Applied Mathematics)
Finite element solution of unsteady magnetohydrodynamics (MHD) flow of an electrically conducting, incompressible viscous fluid past through porous medium between two parallel plates is presented in the presence of a transverse magnetic field and Hall effect. The results obtained from some test cases are then compared with previous published work using the finite difference method (FDM). Numerical examples show that the finite element method (FEM) gives more accurate results in comparison with the finite difference method (FDM).